The Development of Simulation Training System for Microsoft Office Program for Undergraduate Students - Tanyapornhirun, Nitdanee; Uttamasiriseni, Chutitanrat (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This research is aimed at Microsoft Office-usage simulation development for bachelor’s degree students in a private university and to study the satisfaction results of system development. and to study the satisfaction results of system development. The result of the system’s assessment acquired from three system experts and a group of 50 first-year university students under the business administration faculty of a private university in the academic year of 2564 shows that the overall system evaluation average from the experts was 4.36, at the highest level, and the standard deviation was 0.70. In addition, the result evaluated by the students, in terms of system-usage satisfaction was 4.36, a high satisfaction level, and the web-system layout and appearance were appraised at 3.92, a medium satisfactory level. In addition, the satisfaction rate of web-system usage was 4.14, the highest one. The system experience assessment is rated at 4.36, indicating high-level satisfaction.